Blogosfera: nova territorialidade na formação universitária de professores da educação básica - Resende, Luciano Nobre (2016)
This research has as their object the pedagogical use of the blog. The problem of the investigation consists in verifying, from the massive spread of the blog, in contemporary society, the relevance of its educational use. Blogs have evolved from the content publishing easiness in cyberspace, which allowed the exploration of this new means of communication for various types of audiences, such as teachers. This situation favored the growth of the use of blogs in the virtual space which gave rise the blogosphere, which was later overrun by new type of mercantilist speculation, the monetization of contents, which began to influence the production of blogs. We note that this is the situation pointed out by the authors of the critical theory of society, as a situation conducive to the spread of semiformation to the detriment of cultural formation able to contribute to citizenship development. Through such a situation, we make the following hypotheses about the pedagogical use of the blog: is suffering direct influence of monetization and undertakes pedagogical objectives; its origin oriented to the collective work contributes to the construction of knowledge; It can be a tool to build collective knowledge, in an interdisciplinary way and social value. Therefore our objectives were constituted in analyzing the relevance of the pedagogical use of the blog and its relation with the formation of basic education teachers; contextualize, the blog, the blogosphere and the influence they received from contents monetization; investigate how the blog contributes to the collective construction of knowledge; investigate the use of the blog as a content evaluation instrument, built collectively with interdisciplinary character and social value. Empirical research involves documentary analysis of four teacher’s blogs, themed focused on basic education. We observed that teachers, authors of the analyzed blogs, maintained their pedagogical praxis, even in a favorable environment for semiformation. Therefore we call them bloggers teachers, as analysis category that led us to confirm the hypotheses about the contribution to knowledge building interdisciplinary collectively and social value, but the hypothesis of the influence of monetization was not confirmed because the analyzed blogs did not observe its direct influence that compromise pedagogical objectives.